2019
DOI: 10.1101/660787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resting-state “Physiological Networks”

Abstract: Slow changes in systemic brain physiology can elicit large fluctuations in fMRI time series, which may manifest as structured spatial patterns of temporal correlations between distant brain regions. These correlations can appear similar to large-scale networks typically attributed to coupled neuronal activity. However, little effort has been devoted to a systematic investigation of such "physiological networks"-sets of segregated brain regions that exhibit similar physiological responses-and their potential in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 100 publications
1
17
1
Order By: Relevance
“…2) imply that removal of widely shared variance (e.g., with global signal regression), although useful for enhancing spatial specificity (96), alters rather than eliminates the manifestation of global waves in BOLD time series. The available evidence supports this interpretation (22,51,59). Our results pose a challenge to the commonly held view that BOLD associations with physiological variables, even if related to neuronal activity, are purely a "nuisance" in investigations not explicitly concerned with fluctuating arousal.…”
Section: Implications For Bold Imagingcontrasting
confidence: 44%
See 1 more Smart Citation
“…2) imply that removal of widely shared variance (e.g., with global signal regression), although useful for enhancing spatial specificity (96), alters rather than eliminates the manifestation of global waves in BOLD time series. The available evidence supports this interpretation (22,51,59). Our results pose a challenge to the commonly held view that BOLD associations with physiological variables, even if related to neuronal activity, are purely a "nuisance" in investigations not explicitly concerned with fluctuating arousal.…”
Section: Implications For Bold Imagingcontrasting
confidence: 44%
“…[e.g., (39,(49)(50)(51); see Discussion]. However, our model posits that propagating BOLD signal fluctuations observed with fMRI are physiologically coupled to electrophysiological waves reflecting neuronal activity.…”
Section: Global Waves In Macaque Ecogmentioning
confidence: 98%
“…Large amplitude peaks or transients in the BOLD, however, in addition to neural events may also reflect motion (Power et al, 2012) and physiological noise, such as spontaneous fluctuations in arterial CO2 (Golestani et al, 2016;Prokopiou et al, , 2016, cardiac pulsatility (Glover et al, 2000), respiration and heart rate variability (Birn et al, 2008;Chang et al, , 2009Kassinopoulos and Mitsis, 2019). These non-neuronal sources of BOLD signal variability have been shown to elicit networks of coherent BOLD activity, which resemble previously reported resting-state networks derived from fMRI data (Chen et al, 2019;Nalci et al, 2019;Nikolaou et al, 2016;Shokri-Kojori et al, 2018). In addition, covariation of the BOLD signal in different brain regions that is sufficient to give rise to spatial patterns of resting-state activity can be also observed at the timings of lower amplitude peaks, or even at regularly or randomly selected timepoints along the time course of the signal.…”
Section: Introductionsupporting
confidence: 73%
“…Moreover, recent studies in the fMRI literature investigated a large number of fMRI preprocessing pipelines and pointed out that no preprocessing pipeline offers a perfect noise free signal (Parkes et al, 2018). Also, other studies showed that the network structure elicited by non-neural sources of BOLD signal variability is conformable to the structure of previously reported resting-state networks (Bright and Murphy, 2015;Chen et al, 2019;Nalci et al, 2019). On account of these considerations, we believe that the contribution proportion of neural versus non-neural sources in the high amplitude peaks of the BOLD cannot be easily elucidated.…”
Section: Lower-amplitude Co-fluctuations In Bold-fmri Contribute To Rmentioning
confidence: 82%
“…Modelling of respiratory influences on BOLD signal fluctuations is nontrivial, as respiratory response functions often fail to capture the impact of pauses and subtle variations in rate and depth of breathing [42,78]. Recently, it has also been shown that resting-state BOLD signal fluctuations that track respiratory dynamics exhibit spatially heterogeneous time courses (lags and shape) throughout the brain [82]. Thus, we cannot fully rule out respiratory mechanisms underpinning our observed time of day effects on BOLD signal fluctuation.…”
Section: Respiratory Variation Also Shows Time Of Day Modulation But mentioning
confidence: 89%